2016
DOI: 10.1074/jbc.m116.729517
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous N-terminal Domain Cleavage Modulates α1D-Adrenergic Receptor Pharmacodynamics

Abstract: The ␣ 1D -adrenergic receptor (ADRA1D) is a key regulator of cardiovascular, prostate, and central nervous system functions. This clinically relevant G protein-coupled receptor has proven difficult to study, as it must form an obligate modular homodimer containing the PDZ proteins scribble and syntrophin or become retained in the endoplasmic reticulum as nonfunctional protein. We previously determined that targeted removal of the N-terminal (NT) 79 amino acids facilitates ADRA1D plasma membrane expression and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 54 publications
3
24
0
Order By: Relevance
“…In all conditions, the NT forms a lid over the extracellular vestibule and is in direct interaction with SB269652, suggesting a previously unappreciated role of the NT in ligand binding at D2R and D3R. Indeed, the functional roles of the NT have been documented recently in a few closely related homologs, including the α 1D -adrenergic [ 27 ], 5-HT 2B [ 28 ] and μ-opioid receptors [ 29 , 30 ]. By systematically examining all the available high-resolution crystal structures of class-A GPCRs bound to small compounds, we found 9 structures of 6 receptors showing direct interactions (within 5 Å of the heavy atoms) between NT residues and the small-molecule ligands that at least partially occupy the OBS.…”
Section: Discussionmentioning
confidence: 98%
“…In all conditions, the NT forms a lid over the extracellular vestibule and is in direct interaction with SB269652, suggesting a previously unappreciated role of the NT in ligand binding at D2R and D3R. Indeed, the functional roles of the NT have been documented recently in a few closely related homologs, including the α 1D -adrenergic [ 27 ], 5-HT 2B [ 28 ] and μ-opioid receptors [ 29 , 30 ]. By systematically examining all the available high-resolution crystal structures of class-A GPCRs bound to small compounds, we found 9 structures of 6 receptors showing direct interactions (within 5 Å of the heavy atoms) between NT residues and the small-molecule ligands that at least partially occupy the OBS.…”
Section: Discussionmentioning
confidence: 98%
“…In recombinant systems, α 1D ‐ adrenoceptors are mainly misfolded or unable to undergo proper ligand binding and intracellularly located due to a motif present within the first N‐terminal 79 amino acids of the receptor (Hague, Chen, et al, ; Hague, Uberti, et al, ; Pupo, Uberti, & Minneman, ). Recent evidence has indicated that N‐terminal proteolysis of the α 1D ‐ adrenoceptors could be an endogenous mechanism for proper plasma membrane expression (Kountz et al, ). To increase membrane expression of this receptor, we used N‐terminally truncated receptors with additional mutations in the third intracellular loop and C‐tail to gain insights on the phosphorylated residues.…”
Section: Regulation Of α1‐adrenoceptors By Phosphorylationmentioning
confidence: 99%
“…When expressed, it exhibits a predominant intracellular location [ 119 ], which seems be due to a domain located at the amino terminus [ 120 , 121 , 122 ]; therefore, amino terminus truncation is a suitable experimental procedure to achieve α 1D -adrenoceptor expression at the plasma membrane [ 96 , 114 , 120 , 121 , 122 ]. Interestingly, recent detailed work has shown, using receptor affinity purification and MS, that in multiple human cell lines, α 1D -adrenoceptors are expressed both as the full-length form and also as an amino terminus-truncated protein [ 123 ]. A cleavage site was identified at the L910/V91 site, and it was suggested that the proteolytic processing of the amino terminus is a physiological mechanism to achieve membrane location of α 1D -adrenoceptors with optimal functional properties [ 123 ].…”
Section: Tales Of Three Gpcrsmentioning
confidence: 99%
“…Interestingly, recent detailed work has shown, using receptor affinity purification and MS, that in multiple human cell lines, α 1D -adrenoceptors are expressed both as the full-length form and also as an amino terminus-truncated protein [ 123 ]. A cleavage site was identified at the L910/V91 site, and it was suggested that the proteolytic processing of the amino terminus is a physiological mechanism to achieve membrane location of α 1D -adrenoceptors with optimal functional properties [ 123 ].…”
Section: Tales Of Three Gpcrsmentioning
confidence: 99%